Pengaruh Media Sosial terhadap Kemampuan Berbahasa Indonesia di Kalangan Generasi Muda - Putri, Andi Adilah Maharani; Erza, Nela; Ameliyah, Rezki; Haliq, Abdul (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Language plays an important role as a fundamental communication system in social interaction and the formation of cultural identity. This study examines the impact of social media on the Indonesian language skills of the younger generation. The rapid emergence of social media, especially among teenagers, has significantly changed the use of Indonesian. Direct observation was conducted to analyze writings on social media and compare them with the Enhanced Spelling (EYD) guidelines. Findings from direct observation showed that younger people tend to use slang, foreign terms, and abbreviations that do not always follow standard Indonesian language rules. However, social media also has a positive impact by introducing language variations and promoting Indonesian culture on the global stage. Therefore, it is very important for the younger generation to use social media responsibly, so that they can remain productive and love Indonesian. In the digital context, social media has become a new space that influences the way the younger generation uses Indonesian. This study aims to examine how the use of Indonesian by the younger generation is influenced by social media, especially in terms of conformity with standard language rules. The method used is a qualitative analysis of 150 posts from social media users aged 15-24 years on the Instagram and Twitter platforms, collected during the period January-March 2024. The data was analyzed by comparing the linguistic elements in the posts with the Enhanced Spelling (EYD) guidelines. The results of the study showed that 78% of the posts contained elements of non-standard language, such as the use of abbreviations ("bgt", "gak"), slang ("lo", "gue"), and foreign terms ("update", "cringe"). However, creative practices were also found in the use of language that reflected group identity and the promotion of local culture. These results indicate that social media has an ambivalent role: on the one hand, it shifts standard language norms, but on the other hand, it opens up space for new linguistic dynamics and expressions. Therefore, it is necessary to strengthen Indonesian language literacy that is adaptive to the development of digital media.